Association between genetically predicted leukocyte telomere length and non-scarring alopecia: A two-sample Mendelian randomization study - Li, Yicheng; Yang, Shuting; Liao, Minjun; Zheng, Zijun; Li, Mengyao; Wei, Xuerong; Liu, Mengqian; Yang, Lei (Frontiers in Immunology, 2023)
Background: Most commonly acknowledged non-scarring alopecia include androgenetic alopecia (AGA) and alopecia areata (AA). Previous studies revealed various risk factors associated with alopecia. However, relationship between leukocyte telomere length (LTL) and non-scarring alopecia remains unclear. Methods: A two-sample Mendelian Randomization (MR) analysis was performed to evaluate the causality between genetically predicted LTL and risk of non-scarring alopecia. The MR analyses were performed using the Inverse-variance weighted (IVW) method and complemented with other MR methods. Results: Summary statistics of genome-wide association studies (GWAS) for AGA and AA were obtained from the FinnGen biobank, with 119,185 and 211,428 individuals involved, respectively. 126 single-nucleotide polymorphisms (SNPs) with genome-wide significance were selected as instrumental variables for LTL. The MR analyses suggested a causal relationship between LTL and AGA, and the risk of AGA increased by 3.19 times as the genetically predicted LTL shortened by one standard deviation under the IVW method (OR = 4.19, 95% confidence interval: 1.20 - 14.61, p = 0.024). Other MR methods demonstrated a similar trend of the effect of LTL on AGA as well. There is no causal relationship between LTL and AA (p > 0.05). Sensitivity analyses further demonstrated that the current results were less likely to be affected by confounders and bias. Conclusion: Our results suggested the potential causal relationship between LTL and AGA, and shortened LTL was associated with increased risk of AGA.